Incorporating technologies into a flexible teaching space. (8th May 2013) - Joy, Mike; Foss, Jonathan; King, Emma; Sinclair, Jane; Sitthiworachart, Jirarat; Davis, Rachel
Abstract Higher education institutions are increasingly exploring how they can use emerging technologies to develop and enhance the learning experiences offered to students. These activities have mainly focused on developing student‐centred facilities. The University of Warwick has taken the next step by developing a space (the Teaching Grid) specifically designed to meet the needs of teaching staff across the institution. This paper describes how the Teaching Grid supports teachers by providing a flexible experimental space together with a rich collection of established and new technologies, and with comprehensive staff support. We analysed the use of the facility during the first 30 months of operation, using data collected from 119 case studies, in order to present a perspective on how they have used the technologies and how this has impacted on their teaching practice. We present a taxonomy that provides a concrete framework to support future analysis of and comparisons between such spaces.